(untitled) (Hematology Meeting Reports, 2009)
umor vasculature and neoangiogenesis have recently become promising targets for antineoplastic therapy. Antiangiogenic agents act by preventing the formation of new vessels, while vascular targeting drugs cause a selective damage of already formed tumor blood vessels. In order to maintain their efficacy, antiangiogenic compounds need to be administered continuously. They are mainly used in association with standard chemotherapies, raising a critical question about their safety and toxicity, as shown by the first clinical trials with these agents, in which thrombotic or hemorrhagic events emerged as important complications.